An integrated network analysis, RNA-seq and in vivo validation approaches to explore the protective mechanism of Mongolian medicine formulae Ruda-6 against indomethacin-induced gastric ulcer in rats - Feng, Lan; A., Lisha; Bao, Terigele; Mu, Xiyele; Ta, Na; Duan, Qiang; Ta, La; Chen, Yongsheng; Bai, Laxinamujila; Fu, Minghai (Frontiers in Pharmacology, 2023)
Gastric ulcer (GU) is one of the most prevalent digestive diseases that seriously affects people's health. Previous studies have demonstrated the anti-GU effect of Ruda-6 (RD-6), a classic formulae of traditional Mongolian medicine. However, the underlying mechanism of RD-6 against GU remains elusive. Thus, we conducted an integrative approach of network analysis, RNA-seq, and in vivo validation experiment to elucidate the therapeutic mechanisms of RD-6 in preventing GU. A network analysis was performed to predict the potential targets of RD-6. Rats were pretreated with RD-6 at different doses for 21 days, followed by GU induction with indomethacin injection. The ulcer index and inhibition rates were calculated, and the levels of inflammatory related factors were determined by ELISA. The gastroprotective mechanism of RD-6 against ulceration was verified by RNA-seq and the key pathway was detected by in vivo validation. As the network analysis predicted, RD-6 exerts anti-GU effects by regulating 75 targets and 160 signaling pathways. Animal experiment results suggested that pretreatment with RD-6 significantly ameliorated the gastric mucosal injury and inflammatory response, as evidenced by a reduced ulcer index, decreased interleukin (IL)-1β, IL-6 and IL-17 levels, and increased prostaglandin E2 (PGE2) levels in the GU model rats induced by indomethacin. RNA-seq data identified four potential hub genes that were primarily involved in the IL-17 signaling pathway. Furthermore, in vivo validation experiment showed that RD-6 inhibited the IL-17 signaling pathway by down-regulating the expression of IL17RA, proto-oncogene C-Fos (FOS), IL1B and prostaglandin-endoperoxide synthase 2 (PTGS2). Taken together, the present study This is a provisional file, not the final typeset article provides evidence that RD-6 could effectively protect against indomethacin-induced GU, which might be attributed to suppressed inflammation. The IL-17 signaling pathway may be one of the crucial mechanisms that mediates the effect of RD-6.